Youth perspectives on mental health during COVID-19 lockdown in a Small Island Developing State: implications for emergency response - Murphy, Madhuvanti M.; Pemberton, Cecile; Wheeler, Erica; Gulston, La Donna; Kerr-Layne, Odessa; John, Ayana; Baksh, Beverly; Thomas, Gail; Allen, Caroline F. (Frontiers in Psychiatry, 2024)
Introduction Evidence exploring the relationship between COVID-19 mitigation measures and mental health has primarily been from quantitative studies in large, developed countries. A qualitative study to explore the knowledge, attitudes and behaviors of young people living in Trinidad and Tobago was conducted to engage and collaborate with youth on matters affecting them during the pandemic. Methods Ten virtual focus groups were conducted with 64 participants aged 18 to 24 in 2021 when partial lockdown measures were in effect for COVID-19 prevention. Groups were stratified by geographic location and socioeconomic status. The recordings were transcribed and analyzed to explore themes of importance to youth. Results Negative impacts on mental health emerged as a strong theme. Lack of timelines for restrictions led to wide ranging mental health impacts, conflict and tension existed in home environments, longer restrictions led to erosion of the social culture, and young people experienced stress about the changing face of education and job security due to the pandemic. Discussion Measures taken to address one serious public health concern, COVID-19, led to the aggravation of another serious public health concern, mental ill-health. Mental health initiatives to help young people navigate issues specific to their generation must be developed. In low resourced Small Island Developing States settings. The increased need for mental health services during and because of the COVID-19 pandemic highlights the need for strengthening the capacity and resilience of these to respond to environmental and health emergencies. Building the resilience of educational and employment services is also needed.